2014
DOI: 10.7243/2052-9341-2-1
|View full text |Cite
|
Sign up to set email alerts
|

An unusual casein kinase 1 from Trypanosoma cruzi epimastigotes

Abstract: Background: CK1 enzymes are serine/threonine protein kinases that regulate numerous cellular processes. Although seven putative CK1 ortholog genes have been identified in the genome of Trypanosoma cruzi, the causative agent of Chagas' disease, only two parasite CK1 isoforms have been characterized to date. Methods: T. cruzi epimastigotes were collected at the exponential phase of growth. The parasite clarified cytosolic fraction was separated by anion-exchange column chromatography, and the non-adsorbed fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In our study, emodin showed specific submicromolar inhibition of parasite release in CHO cells. Emodin was previously only tested on epimastigotes at high micromolar concentrations (94) where it inhibited casein kinase 1 with an IC 50 value of 130 µM (95), thus significantly less potent than in the trypomastigote infection assay shown here. Other reported effects of this natural product include antiinflammatory, antiosteoporosis, and antidepressant effects (93).…”
Section: Sar Study Of Anthraquinones As Antichagasic Natural Productsmentioning
confidence: 84%
“…In our study, emodin showed specific submicromolar inhibition of parasite release in CHO cells. Emodin was previously only tested on epimastigotes at high micromolar concentrations (94) where it inhibited casein kinase 1 with an IC 50 value of 130 µM (95), thus significantly less potent than in the trypomastigote infection assay shown here. Other reported effects of this natural product include antiinflammatory, antiosteoporosis, and antidepressant effects (93).…”
Section: Sar Study Of Anthraquinones As Antichagasic Natural Productsmentioning
confidence: 84%
“…In our study, emodin showed specific inhibition of T. cruzi parasite release in CHO cells in the nanomolar or low micromolar range, depending on host cell culture condition. Emodin has been tested previously only on epimastigotes at high micromolar concentrations ( De Lima et al, 2017 ) and as weak inhibitor of casein kinase 1 with an IC 50 value of 130 μM ( Justiniano et al, 2014 ). Other reported effects of emodin include anti-inflammatory, antiosteoporosis, anti-cardiovascular disease, and antidepressant effects ( Li and Jiang, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CK substrate CK-S (sequence = (RRKHAAIG(pS)AYSITA, where pS corresponds to phosphorylated serine) is a substrate for CK2 in L. donovani , [102]. Pep1 (sequence = RRKDLHDDEEDEAMSITA) and Pep2 (sequence = RRRADDSDDDDD) are selective substrates for CK1 and CK2, respectively, and not only have been used as substrates for new kinase activity, but have also been used to sub-classify CKs identified from parasites kinetoplastids [104-109, 111113] and apicomplexans [33, 110, 114]. DDDEESITRR and KRRRAL(pS)VASLPGL [110] have also been used as CK1-specific peptide substrates, and RRREEE TEEE [110], RRREDEESDDEE, eIF2β-derived peptide MSGDEMIFDPTMSKKKKKKKKP [114] and RRASADDSDDEDL [115] have also been used as a CK2-specific peptide substrates.…”
Section: Homology and Known Functional Substrates Of Homologuesmentioning
confidence: 99%
“…DDDEESITRR and KRRRAL(pS)VASLPGL [110] have also been used as CK1-specific peptide substrates, and RRREEE TEEE [110], RRREDEESDDEE, eIF2β-derived peptide MSGDEMIFDPTMSKKKKKKKKP [114] and RRASADDSDDEDL [115] have also been used as a CK2-specific peptide substrates. Typical Pep1 concentrations for activity assays are 100 – 800 μM [104-108, 113], while Pep2 concentrations usually range 40 -200 μM [33, 104109, 112, 113]. Recombinant CK1.1 from T. cruzi had apparent Km for β-casein of 5.7 mg/mL and for Pep1 of 128 μM [108].…”
Section: Homology and Known Functional Substrates Of Homologuesmentioning
confidence: 99%